Cross-species analysis of viral nucleic acid interacting proteins identifies TAOKs as innate immune regulators - Friederike L. Pennemann (Nature Portfolio, 2021)
Whether there are conserved nucleic acid (NA) binding proteins across species is not fully known. Using data from human, mouse and fly, the authors identify common binders, implicate TAOKs and show that these kinases bind NAs across species and promote virus defence in mammalian cells.